Rondas infantiles y la comunicación oral en niños de la Institución Educativa Inicial N° 713, Yavarí 2025 - Barboza Neco, Cindi Yojana (2025)
The purpose of this research was to analyze the relationship between the implementation of children's rounds and the development of oral communication in children at Yavarí Early Childhood Education Institution No. 713, during the year 2025. The study was framed within a quantitative, basic approach and with a correlational design. The population consisted of 68 children from the initial level. For data collection, the observation technique was used, using a structured guide as an instrument validated through expert judgment. The results obtained through Spearman's Rho coefficient showed a positive correlation of moderate level (r = 0.551), which indicates that the more adequately implemented children's rounds are, the higher the level of development of oral communication in children. Furthermore, the bilateral significance value (p = 0.05) confirmed the existence of a statistically significant relationship between both variables with a confidence level of 95%, which allowed us to accept the research hypothesis. In conclusion, the study demonstrates that nursery rhymes not only encourage children's active participation, but also represent a valuable pedagogical strategy for stimulating oral language from an early age.